Radio-frequency plasma potential variations originating from capacitive coupling from the coil antenna in inductively coupled plasmas - Watanabe, M., author; Collins, George J., author; Shaw, D. M., author; Sugai, H., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1999)
The radio-frequency plasma potential in a stove top inductively coupled plasma source is measured by a capacitive probe. The experimental results are compared to a crude circuit model which accounts for capacitive coupling between the rf coil and the bulk plasma. The capacitive coupling model has three terms: the dielectric window capacitance, the sheath capacitance between the dielectric window and the bulk plasma, and the bulk plasma to ground sheath capacitance. The crude circuit model predictions are verified by quantitative comparison with the measured rf plasma potential in the bulk argon plasma at pressures from 1 to 20 mTorr and radio-frequency (13.56MHz) plasma power levels from 60 to 1000 W. Finally, the measured ion energy spectrum, as determined by a retarding potential analyzer, agrees with rf plasma potential measurements over the entire range of experimental conditions.